Association between body mass index and insulin resistance in survivors of pediatric acute lymphoblastic leukemia. (2020) - Bahoush, Gholamreza; Salajegheh, Pourya; Rohani, Farzaneh
Abstract: In this retrospective cohort study, oral glucose tolerance testing (OGTT) was performed for all enrolled survivors of patients who suffered from acute lymphoblastic leukemia (ALL) at least 9 months after ending chemotherapy, as well as for control group. All demographic, treatment and anthropomorphic data were obtained from medical records. Furthermore, insulin resistance was evaluated according to insulin level, Matsuda and HOMA-IR index. Of 53 subjects, 28 exhibited B-cell ALL, and 25 were healthy children (F/ M  = 1.12/1). Mean age (±SD) was determined to be 10.77 ± 2.83 years, and meantime off for therapy was also recorded as 3.0 ± 1.6 years. ALL patients were diagnosed at age 1–15 years; none of them received the cranial radiotherapy, and demographic characteristics (age, sex, and sexual maturity) were found to be the same in both groups. Seven patients showed transient hyperglycemia during ALL treatment, however, no significant differences were found in terms of body mass index (BMI) means between ALL patients with and without transient hyperglycemia. Based on the data presented herein, insulin resistance could not be predicted by glucose levels during therapy, cumulative asparaginase, and steroid. Our findings demonstrated that elevated BMI could be a valuable predictor of insulin resistance probability in ALL patients. The presence of transient hyperglycemia does not appear to be associated with the increased risk of glucose intolerance or insulin resistance in the first few years after completion of therapy.